Penerapan Model Active Learning terhadap Keaktifan Belajar Siswa dalam Pembelajaran Pendidikan Pancasila di SDN Gebanganom - Dian Luthfi Kusumawardani; Syifa Rifdatul Khusna; Susilo Tri Widodo; Heni Puji Astuti (STKIP Subang, 2025)
This study aims to examine the implementation of Pancasila Education learning at Gebanganom Elementary School, identify obstacles to the learning process, and implement innovative, contextual learning practices for elementary school students. The research method used was descriptive qualitative, using observation, interviews, and direct learning practices. The results indicate that learning is still dominated by lecture methods and limited media use. Students' limited literacy and numeracy skills also influence their understanding of the material. Through innovative learning practices such as discussions, simulations, and project activities, students demonstrated greater enthusiasm and a better understanding of Pancasila values. In conclusion, Pancasila Education learning will be more effective if presented contextually, using engaging media, and actively involving students.